Awareness and correlates of noticing changes to cigarette packaging design after implementation of the European Tobacco Products Directive: findings from the EUREST-PLUS ITC Europe Surveys. (12th September 2020) - Kyriakos, Christina N; Driezen, Pete; Girvalaki, Charis; Hitchman, Sara C; Filippidis, Filippos T; Gravely, Shannon; Balmford, James; Nikitara, Katerina; Mons, Ute; Fernández, Esteve; Przewoźniak, Krzysztof; Trofor, Antigona C; et al.
Abstract: Background: The European Tobacco Products Directive (TPD), which went into effect in May 2016, regulates packaging design and labelling of cigarettes and roll-your-own (RYO) tobacco. The aim of the current study was to examine whether smokers and recent quitters in six European Union (EU) countries (Germany, Greece, Hungary, Poland, Romania and Spain) reported noticing TPD-related changes to packaging, and correlates of noticing these changes. Methods: Cross-sectional data from the Wave 2 of the ITC 6 European Country Survey in 2018 after implementation of the TPD. Bivariate analyses included adult smokers ( n = 5597) and recent quitters ( n = 412). Adjusted logistic regression analyses were restricted to the subset of current smokers ( n = 5597) and conducted using SAS-callable SUDAAN. Results: Over half of smokers (58.2%) and 30% of quitters noticed at least one of five types of TPD-related pack changes. Over one-quarter of all respondents noticed changes to health warnings (30.0%), standardized openings (27.7%), minimum pack unit size (27.9%), and the removal of tar, nicotine and carbon monoxide information (26.7%) on packaging. Cross-country differences were observed across all measures, with noticing all pack changes markedly lower in Spain than the other countries. Correlates of noticing specific pack changes included sociodemographic characteristics, smoking behaviours and related to packaging. Conclusions: This is one of the first cross-country studies to examine the extent to which TPD changes to cigarette and RYO tobacco packaging are being noticed by smokers and recent quitters. Findings indicate that the majority of smokers noticed at least one type of pack change, but this varied across countries and sub-populations.